A graphene oxide nanosensor enables the co-delivery of aptamer and peptide probes for fluorescence imaging of a cascade reaction in apoptotic signaling. Issue 1 (30th November 2017) - Liu, Chang; Hu, Yan-Lei; Deng, Wen-Jing; Pan, Qing-Shan; Yi, Jin-Tao; Chen, Ting-Ting; Chu, Xia
Abstract : Cytochrome c (Cyt c) and caspase-3 are the key mediators in apoptotic signaling. Abstract : Cytochrome c (Cyt c) and caspase-3 are the key mediators in apoptotic signaling. As is known to all, the release of Cyt c from mitochondria is a vital caspase activation pathway and defines the point of no-return in cell apoptosis. However, it has not been reported that any fluorescence imaging tools could allow simultaneous visualization of Cyt c translocation and caspase-3 activation in apoptotic cells. Here, we develop a sensitive nanosensor that holds the capability of imaging of the released Cyt c from the mitochondria and a caspase-3 activation cascade reaction in apoptotic signaling. The nanosensor is constructed by the assembly of a fluorophore (Cy5)-tagged DNA aptamer on graphene nanosheets that have been covalently immobilized with a FAM-labeled peptide. After a spatially selective delivery into the cytoplasm, the Cy5-tagged DNA aptamer assembled on the nanosensor can bind with Cyt c released from the mitochondria to the cytoplasm and dissociate from graphene, triggering a red fluorescence signal. In addition, the caspase-3 activated by the Cyt c released to the cytoplasm can cleave the FAM-labeled peptide and result in a green fluorescence output. The nanosensor exhibits rapid response, high sensitivity and selectivity for in vitro assays, and high contrast imaging of Cyt c and caspase-3 in living cells. It also provides the method for the study of the kinetic relationship between the Cyt c translocation and caspase-3 activation through simultaneous imaging of Cyt c and caspase-3. The developed nanosensor described here will be an efficient and potential platform for apoptosis research.